A influência do comprometimento prévio na escolha do consumidor - Demoliner, Sergio Silva (2017)
Researchers of social psychology and marketing professionals have historically demonstrated interest in understanding the psychological processes involved in the techniques applied to influence consumer choice. The effect of previous commitment as an influencer on choice behavior (CC effect) was largely studied in the field of social influence. However, studies of the CC effect have been limited to the influence caused in consumer choice when he chooses for himself and neglected when he chooses for other people. Authors in the field of consumers choices have studied the differences between choosing for themselves versus choosing for others, justified by the psychological distance (CLT – Construal Level Theory). Studies that analyzed the relations between both theories (CC and CLT) are rare. Some evidences demonstrated the moderator effect of the psychological distance (in its temporal dimension) on the CC effect. The present study aimed to analyze the effect of previous commitment on consumer choice (CC) not only for himself but for others and to check if the social dimension of the psychological distance also plays a role of moderator in the CC effect. For this study it was developed an experiment 2 (Commitment: Yes versus No) x 2 (Type of Decision: for Himself versus for Others) with 180 American participants (between subjects). The experimental group was driven to a commitment manipulation favorable to a healthy cause. There after all the participants were exposed to a choice simulation when they could choose a healthy or an indulgent product. Half of the group was asked to make a choice for themselves and the other half was asked to make a choice for another person. The data was analyzed using logistic regression and “t” test, according to the type of analysis required. The results demonstrated that the CC effect occurs not only when the consumer chooses for himself but also when he chooses for others. However, the moderator effect of social dimension of psychological distance (CLT) in the CC effect was not confirmed. From these evidences it can be inferred that the previous commitment can be an efficient technique to influence people to make healthier food choices, specially due to the frequency consumers buy food for other people (ex. Family fathers or mothers).